Factors influencing care-seeking delay or avoidance of heart failure management: A mixed-methods study. (August 2020) - Ivynian, Serra E.; Ferguson, Caleb; Newton, Phillip J.; DiGiacomo, Michelle
Abstract: Background: Delayed care-seeking for heart failure symptoms increases the risk of unplanned and frequent hospitalization. Presenting to hospital at a later stage when symptoms are severe requires more complex treatment, contributing to longer lengths of stay and higher risk of mortality. Patient-related factors such as knowledge have been highlighted as key contributors to care-seeking delay, yet little is known about how previous experiences within the healthcare setting, including relationships with providers, influence decisions to engage with health services when required. Objective: To assess patient-related factors thought to impact care-seeking, and examine the role of previous healthcare experiences in decisions to seek or avoid professional care. Design: Sequential mixed-methods study with a phenomenological approach. Settings: A cardiology in-patient ward in a quaternary referral hospital in Sydney, Australia. Participants: A total of 72 symptomatic in-patients diagnosed with heart failure. Methods: Self-efficacy, heart failure knowledge and health literacy were assessed quantitatively. Semi-structured, in-depth interviews were undertaken with a subset of participants to elicit previous healthcare experiences and their influence on seeking care when symptoms worsened. Qualitative data were analyzed using interpretative phenomenological analysis and interpreted in the context of quantitative findings. Results: Three major themes were identified that impacted decisions to seek or avoid professional care: (i) preference for continuity; (ii) previous hospital experience and; (iii) patient-provider relationships. Avoidance of care-seeking was described, despite quantitative data reflecting high levels of self-efficacy, heart failure knowledge (12.3±1.9 out of 15), and above-average health literacy levels (75% adequate – 15% higher than average in heart failure). The qualitative and quantitative data together demonstrate that participants delayed seeking care for heart failure symptoms despite having sound knowledge and self-efficacy to seek professional care when necessary. Conclusion: Previous healthcare experience affects patient's subsequent action, despite having skills and heart failure knowledge. Interactions with the healthcare system and those within it may impact decisions to avoid seeking treatment more than patient-related factors such as condition-specific understanding.